2020
DOI: 10.3390/atmos11090906
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Precipitation with Different Intensity on PM2.5 over Typical Regions of China

Abstract: Atmospheric aerosol pollution has significant impacts on human health and economic society. One of the most efficient way to remove the pollutants from the atmosphere is wet deposition. This study selected three typical atmospheric pollution regions in China, the Beijing-Tianjin-Hebei (BTH), the Yangtze River Delta (YRD) and the Pearl River Delta (PRD) regions, as research areas, and used the hourly precipitation and PM2.5 mass concentration data from 2015 to 2017 to investigate the removal impacts of precipit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 39 publications
1
29
0
Order By: Relevance
“…The hourly average precipitation during the pollution events is slightly lower than that during the clean events, which might imply a slightly stronger precipitation scavenging effect during the time for clean events. However, the light precipitation during the study periods could also cause a positive effect to air pollution due to the aerosol hygroscopic growth [21,22]. It is challenging to quantify the influence of precipitation, however, it might be reliable to assume a weak or even negligible influence from precipitation considering its low amount.…”
Section: Meteorological Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The hourly average precipitation during the pollution events is slightly lower than that during the clean events, which might imply a slightly stronger precipitation scavenging effect during the time for clean events. However, the light precipitation during the study periods could also cause a positive effect to air pollution due to the aerosol hygroscopic growth [21,22]. It is challenging to quantify the influence of precipitation, however, it might be reliable to assume a weak or even negligible influence from precipitation considering its low amount.…”
Section: Meteorological Analysismentioning
confidence: 99%
“…Many previous studies have investigated the formations, characteristics, and sources of air pollutants [14][15][16][17][18][19], but the challenges to untangle the effects of Atmosphere 2021, 12, 267 2 of 15 emissions, meteorology and topography make the science community still lack sufficient understanding about the formation and development of air pollution. In addition, the air pollutants could be removed from the atmosphere by dry and wet depositions [20][21][22], and get dispersed by increased winds and planetary boundary layer heights [14]. The lockdown measures during the COVID-19 period provide us an opportunity to investigate the potential effects of emission reduction on air quality, along with the effects of meteorology on air pollution events.…”
Section: Introductionmentioning
confidence: 99%
“…Another factor underlying infiltration is meteorological conditions, such as precipitation, wind speed, wind direction, temperature, and relative humidity. Some studies have reported that wind speed, temperature, and ambient relative humidity are negatively correlated with PM 2.5 concentrations and the PM 2.5 indoor–outdoor ratio [ 17 , 18 , 19 , 20 ]. Precipitation is also inversely proportional to PM 2.5 concentrations, due to the removal effect where particulate matter is removed from the air to the surface by rain [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…No matter it is PM 3.3 or reconstructed mass the background aerosol concentrations were all lower than the mixed and anthropogenic aerosol concentrations. In the wet season, the results are more obvious due to the effects of precipitation, high temperature and high humidity (Sun et al., 2019; Zhao, Sun, et al., 2020). In background aerosol type, the concentrations of major TWSI and carbonaceous species were 26.9 and 26.2 μg/m 3 in dry and wet seasons, respectively, which was significantly lower than the anthropogenic type values of 49.9 and 42.8 μg/m 3 .…”
Section: Resultsmentioning
confidence: 99%